Charles BETTELHEIM, Cultural Revolution and Industrial Organization in China Changes in management and the división of labor. New York, Monthly Review Press, 1974, 128 pp. - Juárez Coqueiro, Pinheiro (Estudios de Asia y África, 1980)
-